2012
DOI: 10.1097/igc.0b013e318234f9ee
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy-Induced Nausea and Vomiting on Quality of Life in Indonesian Patients With Gynecologic Cancer

Abstract: Patients reported a negative impact on the QoL of delayed emesis after chemotherapy. Poor prophylaxis of patients' nausea and vomiting after chemotherapy interferes with patients' QoL. Medical and behavioral interventions may help to alleviate the negative consequences of chemotherapeutic treatment in patients with gynecologic cancers treated with suboptimal antiemetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…It has already been demonstrated that adjuvant chemotherapy and radiotherapy administered after surgery to patients with advanced or high-risk disease can lead to short-or long-term consequences on QOL. 4,5 According to previous studies, women often experience serious disruptions in sexual function after treatment for EC. 6 Surgery and adjuvant radiotherapy can damage sex organs, neuronal structures, and ovarian function, which may seriously impair sexual function.…”
mentioning
confidence: 99%
“…It has already been demonstrated that adjuvant chemotherapy and radiotherapy administered after surgery to patients with advanced or high-risk disease can lead to short-or long-term consequences on QOL. 4,5 According to previous studies, women often experience serious disruptions in sexual function after treatment for EC. 6 Surgery and adjuvant radiotherapy can damage sex organs, neuronal structures, and ovarian function, which may seriously impair sexual function.…”
mentioning
confidence: 99%
“…Severe and poorly controlled CINV was ranked near death by patients undergoing chemotherapy (6). Chemotherapy-induced nausea and vomiting not only has the propensity to increase morbidity, and healthcare cost, but also interferes with the chemotherapy adherence and patient's QoL (9)(10)(11)(12)(13)(14)(15)(16)(17). The current antiemetic agents exert their action by targeting various receptors , neurokinin 1 (NK1), dopamine, etc.]…”
Section: Introductionmentioning
confidence: 99%
“… 1 It has a detrimental effect on the quality of life of patients and their functional well-being. 2 - 4 Uncontrolled nausea or vomiting is also associated with frequent hospital and emergency department visits, is resource consuming, 5 - 8 and can lead to impaired compliance with chemotherapy. 1 , 9 , 10…”
Section: Introductionmentioning
confidence: 99%